Beyond Isolated and Associated: A Novel Fetal MR Imaging–Based Scoring System Helps in the Prenatal Prognostication of Callosal Agenesis - Glatter, S.; Kasprian, G.; Bettelheim, D.; Ulm, B.; Weber, M.; Seidl, R.; Prayer, D.; Diogo, M.C. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: Although “corpus callosum agenesis” is an umbrella term for multiple entities, prenatal counseling is based reductively on the presence (associated) or absence (isolated) of additional abnormalities. Our aim was to test the applicability of a fetal MR neuroimaging score in a cohort of fetuses with prenatally diagnosed isolated corpus callosum agenesis and associated corpus callosum agenesis and correlate it with neurodevelopmental outcomes.MATERIALS AND METHODS: We performed a single-center retrospective analysis of a cohort of cases of consecutive corpus callosum agenesis collected between January 2011 and July 2019. Cases were scored by 2 raters, and interater agreement was calculated. Outcome was assessed by standardized testing (Bayley Scales of Infant and Toddler Development, Kaufman Assessment Battery for Children) or a structured telephone interview and correlated with scores using 2-way ANOVA.RESULTS: We included 137 cases (74 cases of isolated corpus callosum agenesis), imaged at a mean of 27 gestational weeks. Interrater agreement was excellent (0.98). Scores were higher in associated corpus callosum agenesis (P < .0001) without a significant score difference between complete and partial corpus callosum agenesis (P = .38). Outcome was assessed in 42 children with isolated corpus callosum agenesis and 9 with associated corpus callosum agenesis (mean age, 3.1 years). MR imaging scores correctly predicted developmental outcome in 90.7% of patients with isolated corpus callosum agenesis, improving neurodevelopmental risk stratification in corpus callosum agenesis.CONCLUSIONS: The scoring system is very reproducible and can differentiate isolated corpus callosum agenesis and associated isolated corpus callosum agenesis (significantly higher scores) but not between partial and complete corpus callosum agenesis. Scores correlated with outcome in isolated corpus callosum agenesis, but there were too few associated postnatal cases of isolated corpus callosum agenesis to draw conclusions in this group.aCCAassociated corpus callosum agenesisCCcorpus callosumCCAcorpus callosum agenesisDCCdeleted in colorectal canceriCCAisolated corpus callosum agenesisMCDmalformations of cortical developmentTOPtermination of pregnancy